Current approaches to pain assessment and management in the paediatric emergency department - Kłosiewicz, Tomasz; Rozmarynowska, Monika; Suchecki, Piotr; Łasowski, Bartosz; Sytek, Paulina; Michalkiewicz, Wiktoria (Pediatria Polska - Polish Journal of Paediatrics, 2025)
A common problem encountered in hospital emergency departments is inadequate assessment and management of pain in paediatric patients. Research shows that this is a worldwide issue, with younger patients being at greater risk of not receiving appropriate treatment. Poorly managed pain not only worsens patients’ quality of life but also increases mortality and can have negative effects on child development. The aim of this study was to gather and analyse available scientific knowledge on pharmacological and non-pharmacological methods of pain management in children, considering their potential applications in hospital emergency departments. The results of this review might be used to implement optimum strategies for acute pain management, thereby contributing to improved comfort, diagnostic and treatment conditions, and thus quality of care.